The Ship of the Dead - Riordan, Rick (Riordan, Rick. Magnus Chase and the gods of Asgard, 2019)
After Loki escapes, he gathers an army to begin the final battle against the Asgardians. Magnus Chase and his motley group of friends attempt to stop Loki before he can board the "Naglfar," the Ship of the Dead, and launch the Ragnarok, but first they must sail across the oceans of Midgard, Jotunheim, and Niflheim, facing down all manner of beasts and threats before they can even begin to try and outwit Loki.